Congklak-Based Ethnomathematics Learning: A MANOVA Analysis of Motivation and Mathematics Achievement - Syarifah Ivonesti; Nina Zakiah (Educazione: Journal of Education and Learning, 2024)
Many elementary students continue to struggle with mathematics and approach it with anxiety, which weakens both their motivation and their achievement. This study examines the effectiveness of Congklak-based ethnomathematics learning in improving elementary students' mathematics motivation and mathematics achievement through a multivariate approach. The research applied a quantitative method using a quasi-experimental pretest–posttest control group design involving 40 elementary school students, with 20 assigned to the experimental group and 20 to the control group. The experimental group learned mathematics through instruction built around the traditional game of Congklak, whereas the control group received conventional teaching. Mathematics motivation was measured using the Elementary Mathematics Motivation Inventory (EMMI), and mathematics achievement was assessed through a validated achievement test. After all assumptions were confirmed, the data were analyzed using descriptive statistics and multivariate analysis of variance (MANOVA). The findings showed meaningful gains in both motivation and achievement among students taught through Congklak-based ethnomathematics learning. The multivariate test confirmed a significant effect of the instructional approach on both dependent variables (Wilks' Lambda = 0.116; F = 140.391; p < 0.001). These results indicate that weaving a familiar traditional game into mathematics instruction builds a culturally meaningful environment that strengthens motivation and academic performance at once. Consequently, teachers are encouraged to draw on traditional games and local wisdom as practical resources for creating mathematics learning that is more engaging, contextual, and relevant to students' lives.